Analisis Kualitas Pelayanan Surat Ijin Mengemudi Kendaraan Motor (SIM C) di Polres Semarang 2016 - Mila Diansari; Endang Larasati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Bureaucratic reform in a whole of life caused the good governance from various side. The excellent quality of public services being a piority in public sector to fulfilling society needs. The service has impact on public satisfication to services provision. The procurement service of Driving Lisence of Motorcycle (SIM C) is one of task and function of public services that held by Polres Semarang. The purpose study of this research is to analyze the service quality the procurement of Motorcycle Driving License (SIM C) in Polres Semarang. The writer uses Serive Quality method to measure the quality of SIM C services based on principles of public services that refers to transparency, accountability, conditional, participatory rights equality and The balance of rights and obligations. The result show that service has not run optimally. Thus, it could not satisfy the recipient yet. The lacking of dimension is in participation and conditional aspect. The Service by using technology can facilitate the provision of driving license service to conduct Online Service that has not applied yet in Polres Semarang. According to the result, the research is conducted to revamp the complaints from public.